Minimal residual disease and outcome characteristics in infant KMT2A-germline acute lymphoblastic leukaemia treated on the Interfant-06 protocol. (January 2022) - Stutterheim, J.; de Lorenzo, P.; van der Sluis, I.M.; Alten, J.; Ancliffe, P.; Attarbaschi, A.; Aversa, L.; Boer, J.M.; Biondi, A.; Brethon, B.; Diaz, P.; Cazzaniga, G.; et al.
Abstract: Background: The outcome of infants with KMT2A -germline acute lymphoblastic leukaemia (ALL) is superior to that of infants with KMT2A -rearranged ALL but has been inferior to non-infant ALL patients. Here, we describe the outcome and prognostic factors for 167 infants with KMT2A -germline ALL enrolled in the Interfant-06 study. Methods: Univariate analysis on prognostic factors (age, white blood cell count at diagnosis, prednisolone response and CD10 expression) was performed on KMT2A- germline infants in complete remission at the end of induction (EOI; n = 163). Bone marrow minimal residual disease (MRD) was measured in 73 patients by real-time quantitative polymerase chain reaction at various time points (EOI, n = 68; end of consolidation, n = 56; and before OCTADAD, n = 57). MRD results were classified as negative, intermediate (<5∗10 −4 ), and high (≥5∗10 −4 ). Results: The 6-year event-free and overall survival was 73.9% (standard error [SE] = 3.6) and 87.2% (SE = 2.7). Relapses occurred early, within 36 months from diagnosis in 28 of 31 (90%) infants. Treatment-related mortality was 3.6%. Age <6 months was a favourable prognostic factor with a 6-year disease-free survival (DFS) of 91% (SE = 9.0) compared with 71.7% (SE = 4.2) in infants >6 months of age ( P = 0.04). Patients with high EOI MRD ≥5 × 10 −4 had a worse outcome (6-year DFS 61.4% [SE = 12.4], n = 16), compared with patients with undetectable EOI MRD (6-year DFS 87.9% [SE = 6.6], n = 28) or intermediate EOI MRD <5 × 10 −4 (6-year DFS 76.4% [SE = 11.3], n = 24; P = 0.02). Conclusion: We conclude that young age at diagnosis and low EOI MRD seem favourable prognostic factors in infants with KMT2A- germline ALL and should be considered for risk stratification in future clinical trials. Highlights: Prognostic factors for infants with KMT2A- germline acute lymphoblastic leukaemia (ALL) are not well known. Characteristics of 167 uniformly treated infants with KMt2A -germline ALL were analyzed. Young age at diagnosis (<6 months) was associated with better outcome. End of induction minimal residual disease (MRD), rather than end of consolidation MRD, was a prognostic factor for outcome. Combined MRD and genetic-based stratification of KMT2A -g infants should be considered.